English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

thank you!

2007-06-07 15:59:11 · 9 answers · asked by Kae Cie Marie 1 in Science & Mathematics Mathematics

9 answers

(3 - 2i).(3 - 2i)
= 9 - 12 i + 4 i²
= 9 - 12 i - 4
= 5 - 12 i

2007-06-08 01:02:55 · answer #1 · answered by Como 7 · 0 0

Proceed using the basics like: A^2 = A x A and i^2 = -1
(3 - 2i)^2 = (3 - 2i) x (3 - 2i)

= 9 - 6i - 6i + 4(i^2)

= 9 -12i + (-4)

= 5 - 12i

2007-06-07 16:07:56 · answer #2 · answered by Hell's Angel 3 · 0 0

(3-2i)^2= 3*3 -2*3*2i+(2i)^2 (using (a-b)^2 formula)
= 9-12i-4 { (2i)^2 = 2 * 2 * i * i = 4* i * i = -4}
= 5-12i
= 5 + (-12)i

hence a= 5
b= -12

2007-06-07 16:06:26 · answer #3 · answered by shrikant s 2 · 0 0

(3-2i)^2=(3-2i)(3-2i)=3*3 - 3*2i - 2i*3 + (-2i)(-2i)=
=9 - 6i - 6i + 4i*i=9 - 12i + 4i^2=9 - 12i - 4=5 - 12i
a = 5 b = -12

2007-06-07 16:03:36 · answer #4 · answered by Anonymous · 0 0

Multiplying complicated numbers is purely the comparable as multiplying an expression. purely like the way you do: (x+3)(y-4) you employ the FOIL technique. (3 +4i) (2- i) Multiply the 1st term: (3)(2) Multiply the OUTER term: (3)(-i) Multiply the internal term: (4i)(2) Multiply the final term: (4i)(-i) Then including purely about all those words, supplies: 6 - 3i +8i - 4i^2 integrate comparable words: 6 + 5i -4i^2 For the imaginary extensive style i, all of us understand that: i=squareroot(-a million) so, i^2 means: squareroot(-a million)^2 via fact the sq. root and the squared cancels each others consequence: i^2= -a million substituting this to the equation supplies: 6 + 5i -4(-a million) 6 +5i +4 combining comparable words, supplies the purely precise answer: 10 + 5i

2016-11-07 22:07:04 · answer #5 · answered by mcmillian 4 · 0 0

(3 - 2i)(3 - 2i)
9 - 6i - 6i + 4i^2
9 - 12i + 4(-1); remember, i^2 = -1
9 - 12i - 4
5 - 12i

2007-06-07 16:22:37 · answer #6 · answered by jimbob 6 · 0 0

(3-2i)(3-2i)... use FOIL method (first, outside, inside, last)
9-6i-6i-4 =
5 - 12i or 5 + (-12)i.

2007-06-07 16:06:29 · answer #7 · answered by Anonymous · 0 0

(3-i2)^2 = (9-12i+4i^2) = 9-4 -12i = 5 - 12i
Ans: 5-12i

2007-06-07 16:03:57 · answer #8 · answered by telsaar 4 · 0 0

(a-bi)^2=a^2-2abi+b^2(-1)

2007-06-07 16:45:00 · answer #9 · answered by nasser a 2 · 0 0

fedest.com, questions and answers